Emergence of a New Pathogen: A Retrospective Study of HPeV-5 Central Nervous System Disease in Alberta, Canada - Grace George; Lea Restivo; Dolores Freire Jijon; Joan L. Robinson; Kevin Fonseca; Kanti Pabbaraju; Xiaoli Dong; Raymond Tellier; Tarah Lynch; Joseph V. Vayalumkal (Viruses)
Human parechoviruses (HPeVs) are known to cause meningo-encephalitis among neonates and infants. We aimed to describe the epidemiology of HPeVs causing central nervous system infections in Alberta from 2014 to 2019 with comparison of known HPeV-3 and emerging HPeV-5. Genomic analysis was completed on a subset of HPeV-5 strains to understand genetic relatedness to other known strains. All cerebrospinal fluid (CSF) samples in Alberta with detection of HPeVs were identified and a case review of medical records was conducted, retrospectively, to gather demographic and clinical details. Descriptive and analytic statistics were used to describe and compare the characteristics of cases affected by HPeV-3 with HPeV-5. Genome amplification was completed on six HPeV-5 samples. During the study period, 18,882 CSF samples were tested; 56 were positive for HPeV-3 or HPeV-5, and 52 patients were included in this study (40 HPeV-3 cases and 12 HPeV-5). A total of 40% of cases occurred in 2016, and 64% of infections occurred in the months of August to October. The mean age of cases was 18 days for HPeV-5 compared with 26 days for HPeV-3 (p = 0.045). Phylogenetic comparison showed similarity to a recombinant strain reported in Australia. HPeV meningo-encephalitis affected neonates/infants, mostly in late summer/early fall, and genomic sequencing of new strains can contribute to understanding the epidemiology of HPeV infections globally.